Influence of the time‐delay of correction for BDS and GPS combined real‐time differential positioning. Issue 12 (1st June 2016) - Wang, Liang; Li, Zishen; Yuan, Hong; Zhao, Jiaojiao; Zhou, Kai; Yuan, Chao
Abstract : Real‐time differential (RTD) positioning can achieve a real‐time metre‐lever positioning based on the differential correction data from a nearby reference station. However, the time‐delay of correction data is generally unavoidable when receiving it from the reference station in real‐time. Multi‐global navigation satellite system combined positioning has the advantages of improving the positioning availability, continuity and accuracy; however, it remains unknown whether it can effectively overcome the time‐delay of differential correction in RTD positioning. This Letter focus on the tolerance of time‐delay for differential correction in BeiDou global navigation satellite system (BDS) and global positioning system (GPS) combined RTD positioning. Based on a set of static data and a set of dynamic data, the performances of BDS standalone, GPS standalone and BDS and GPS combined RTD positioning by 15 kinds of time‐delay of the differential correction data were studied and compared. The numerical results show that, BDS and GPS combined RTD positioning can tolerate longer time‐delay of the corrections than BDS or GPS standalone positioning for the same requested positioning accuracy.